Cancer Diagnostics and Early Detection Using Electrochemical Aptasensors - Joel Imoukhuede Omage; Ethan Easterday; Jelonia T. Rumph; Imamulhaq Brula; Braxton Hill; Jeffrey Kristensen; Dat Thinh Ha; Cristi L. Galindo; Michael K. Danquah; Naiya Sims; Van Thuan Nguyen (Micromachines, 2022)
The detection of early-stage cancer offers patients the best chance of treatment and could help reduce cancer mortality rates. However, cancer cells or biomarkers are present in extremely small amounts in the early stages of cancer, requiring high-precision quantitative approaches with high sensitivity for accurate detection. With the advantages of simplicity, rapid response, reusability, and a low cost, aptamer-based electrochemical biosensors have received considerable attention as a promising approach for the clinical diagnosis of early-stage cancer. Various methods for developing highly sensitive aptasensors for the early detection of cancers in clinical samples are in progress. In this article, we discuss recent advances in the development of electrochemical aptasensors for the early detection of different cancer biomarkers and cells based on different detection strategies. Clinical applications of the aptasensors and future perspectives are also discussed.